Таксономический анализ рода Ameromicrus (Hymenoptera, Torymidae) - Зерова, М.Д.; Серегина, Л.Я. (Вестник зоологии, 1993)
A revision of the genus, divided into two species groups: violaceus and confluent. 3 species from arid regions of Transcaucasia and Middle Asia arc described as new: A. bouceki sp. 11., A. nikolskayae sp. u., A. ellonicus sp. n.